Theory of Change Workbook: A Step-by-Step Process for Developing or Strengthening Theories of Change - and Salib, Monalisa (USAID, 2022)
While over time theories of change have become synonymous with simple if/then statements, a strong theory of change should actually be a much more detailed, context-specific articulation of how we *theorize* change will happen under a program.